Legal Protection for Marine Hull and Machinery Insurance Policyholders Against Default by Insurance Companies (Study of Decision Number 951/Pdt.G/2023/PN.Jkt Brt) - Alisa Reynamora; Mulhadi Mulhadi; Zulfi Chairi (CV. Cognispectra Publishing, 2026)
Marine hull and Machinery insurance policyholders against claim rejections by insurance companies, as reflected in Decision Number 951/Pdt.G/2023/PN.Jkt.Brt. This study aims to analyze the factors causing default by insurance companies, the legal consequences that arise for policyholders, and the legal considerations of the panel of judges in providing legal protection. The research method used is normative juridical with a descriptive nature, through a statutory approach and a case approach. Data were obtained from a literature review of primary, secondary, and tertiary legal materials, which were analyzed qualitatively with deductive conclusions drawn. The results of the study indicate that rejections of marine hull and machinery insurance claims are caused by, among others, claims for risks not covered by the policy, including those included in policy exclusions, inaccurate information provided by the insured, and the unseaworthy condition of the vessel. However, in Decision Number 951/Pdt.G/2023/PN.Jkt.Brt, the panel of judges emphasized that rejection of claims made without a valid basis for agreement constitutes a form of breach of contract, so that the policyholder has the right to demand compensation for the insurer's failure to fulfill its obligations based on the principle of good faith in the insurance agreement